Research progress on microecology and childhood respiratory infections via the lung-gut axis - He, Zhixuan; Wang, Zixuan; Yin, Jiao; Wang, Qiang (Frontiers in Pediatrics, 2025)
Respiratory tract infections (RTIs) are a complex global public health challenge, with children being the most affected population. Affected children often exhibit gut microbiota-related symptoms, such as dysbiosis, feeding difficulties, and malabsorption. Studies show that the lungs and large intestine share embryological homology and a mucosal immune system, with gut microbiota influencing respiratory health—a phenomenon termed the “lunggut axis” Gut dysbiosis may disrupt respiratory microbiota homeostasis, elevating susceptibility to respiratory infections. Probiotic administration mitigates gut dysbiosis and antibiotic resistance induced by antibiotic overuse. It can also restore the balance of gut microbiota, enhance the immune response and metabolic regulation, and thus prevent and assist in treating respiratory infections and other respiratory diseases. A deeper understanding of the relationship between the lung-gut axis microecology and respiratory infections in children may provide novel insights and approaches for disease prevention, diagnosis, and treatment. This review will describe the normal microecology of the respiratory tract in children, the microecological changes associated with respiratory tract infections in children, and the interactions between the “lung-gut axis” and the use of probiotics. It will also provide an outlook on these topics.